How to catch a tiger: Understanding putting performance on the PGA TOUR - Fearing, D.; Acimovic, J.; Graves, S. C. (Journal of Quantitative Analysis in Sports, 2011)
Existing performance metrics utilized by the PGA TOUR have biases towards specific styles of play, which make relative player comparisons challenging. Our goal is to evaluate golfers in a way that eliminates these biases and to better understand how the best players maintain their advantage.